(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2023)
In this research work, a detailed phytochemical and biological investigation of Aconitum heterophyllum was accomplished. The cold methanolic root extract of A. heterophyllum was subjected to VLC for fractionation over silica gel, which led to the isolation of two compounds 1,1,8,8-trimethyl-4-methylene-decahydro- 1H-cyclopenta-[8]-annulen-1-ol (1) and β-stigmasterol (2). The compounds were characterized by analysis of their 1D and 2D NMR spectral data. Compound 1 is first reported from this plant. The crude extract was screened for antimicrobial activity against several gram-positive and gram-negative bacteria, and fungi using disk diffusion method where significant inhibitory activity was observed. The extract was also tested for cytotoxic property using brine shrimp lethality bioassay, which revealed moderate activity in comparison with the standard anticancer drug, vincristine sulphate. Antioxidant property of the crude methanol extract of A. heterophyllum was determined by the scavenging of the DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical and found moderate antioxidant activity (IC50 = 53.25 μg/mL) when compared to standard antioxidant. Total phenolic and flavonoid content and polyphenolic compound content of the crude extract were determined by HPLC. The isolated compounds 1 and 2 showed dosedependent antiproliferation activity against the vero and lung A549 cells. Dhaka Univ. J. Pharm. Sci. 22(1): 1-10, 2023 (June)